2019
DOI: 10.1103/physrevlett.123.211602
|View full text |Cite
|
Sign up to set email alerts
|

Universal Relaxation in a Holographic Metallic Density Wave Phase

Abstract: In this work, we uncover a universal relaxation mechanism of pinned density waves, combining Gauge/Gravity duality and effective field theory techniques. Upon breaking translations spontaneously, new gapless collective modes emerge, the Nambu-Goldstone bosons of broken translations.When translations are also weakly broken (eg by disorder or lattice effects), these phonons are pinned with a mass m and damped at a rate Ω, which we explicitly compute. This contribution to Ω is distinct from that of topological de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
143
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 67 publications
(167 citation statements)
references
References 89 publications
(162 reference statements)
23
143
1
Order By: Relevance
“…At high temperature, we find that it is quite insensitive to the value of the source . This is in agreement with our earlier result [1] that the phonon mass and damping rate are controlled by λ at leading order (see also [47,49]). At low temperatures, the system quickly becomes more incoherent and relaxation is stronger, which leads to a failure of the relation above as increases, see figure 9.…”
Section: Introductionsupporting
confidence: 93%
See 4 more Smart Citations
“…At high temperature, we find that it is quite insensitive to the value of the source . This is in agreement with our earlier result [1] that the phonon mass and damping rate are controlled by λ at leading order (see also [47,49]). At low temperatures, the system quickly becomes more incoherent and relaxation is stronger, which leads to a failure of the relation above as increases, see figure 9.…”
Section: Introductionsupporting
confidence: 93%
“…4 In [45], we verified that transverse hydrodynamic modes with the dispersion relation (1.1) are present in the spectrum. In [1], we showed that these modes become gapped if a small source is turned on, with a dispersion relation (1.4). We found that Ω Gm 2 Ξ, where Ξ ≡ ξ /(K + G) is defined from the bulk and shear moduli K, G and the longitudinal phonon diffusivity ξ .…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations